Ibn Sina as Synthesizer and Innovator: Transmission and Transformation of Greek Knowledge in Medicine and Philosophy - Fahma Hurrosatud Diyanah; Imron Rossidy (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2025)
Many studies on the transmission of Greek knowledge to the Islamic world emphasize translation movements and educational institutions, often overlooking Ibn Sina’s active role as an intellectual innovator. This study examines Ibn Sina’s position not merely as a transmitter, but as a transformative figure who reinterpreted and developed Greek intellectual heritage. Using qualitative library research, it analyzes primary texts (Al-Qanun fi al-Tibb and Ash-Shifa’) and relevant historical sources to trace patterns of transmission, reinterpretation, and innovation. The findings show that Ibn Sina reformulated ideas from Galen, Aristotle, and Hippocrates through clinical observation, systematic methodology, and a novel metaphysical framework. Al-Qanun fi al-Tibb reflects the integration of empirical medical practice, while Ash-Shifa’ and Mantiq al-Mashriqiyyin demonstrate philosophical developments beyond classical Peripatetic thought. Ibn Sina thus transformed Greek knowledge into a new scientific system that significantly shaped Islamic and Western intellectual traditions.